Deutsche Besatzungsherrschaft in Polen 1939-1945. Annexionspolitik - Bevölkerungstransfer - Terror - Vernichtung [German occupation of Poland 1939-1945. Annexation policy - population transfer - terror - extermination] - Martin, Bernd (Studia Historiae Oeconomicae, 2009)
No other country in Europe was occupied by the Germans for as long as Poland during the Second World War - no other nation made such human and material sacrifices as the Polish nation. Wehrmacht soldiers, special SS troops and other special military units were stationed on Polish territory for almost five and a half years, accompanied by countless numbers of conscripted civilian administrators or those who had voluntarily left for the East, who often used the apparatus of violence and destruction as they saw fit or even quarreled with it. The National Socialists turned Poland into a house of death and brought the Polish people to the brink of their physical existence. Of the 35.1 million people living in the country at the start of the war, around 6 million were no longer alive by the end of the war. The overwhelming majority of them were civilians and victims of German occupation policy, even though the Soviet occupation of eastern Poland, which lasted around 19 months, also left its bloody mark and many Poles, around 100,000, lost their lives in ethnic conflicts with the Ukrainians. The German occupation regime in Poland can at best be compared with a similar approach in Serbia and, from June 1941, in the territory of the Soviet Union, but it does not have a European dimension. Occupied France and occupied Poland are essentially not comparable.